An Evaluation of Training with an Auditory P300 Brain-Computer Interface for the Japanese Hiragana Syllabary - Halder, Sebastian; Takano, Kouji; Ora, Hiroki; Onishi, Akinari; Utsumi, Kota; Kansaku, Kenji (Frontiers in Neuroscience, 2016)
Gaze-independent brain-computer interfaces (BCIs) are a possible communication channel for persons with paralysis. We investigated if it is possible to use auditory stimuli to create a BCI for the Japanese Hiragana syllabary, which has 46 Hiragana characters. Additionally, we investigated if training has an effect on accuracy despite the high amount of different stimuli involved. Able-bodied participants (N=6) were asked to select 25 syllables (out of fifty possible choices) using a two step procedure: first the consonant (ten choices) and then the vowel (five choices). This was repeated on three separate days. Additionally, a person with spinal cord injury (SCI) participated in the experiment. Four out of six healthy participants reached Hiragana syllable accuracies above 70% and the information transfer rate increased from 1.7 bits/min in the first session to 3.2 bits/min in the third session. The accuracy of the participant with SCI increased from 12% (0.2 bits/min) to 56% (2 bits/min) in session three. Reliable selections from a 10×5 matrix using auditory stimuli were possible and performance is increased by training. We were able to show that auditory P300 BCIs can be used for communication with up to fifty symbols. This enables the use of the technology of auditory P300 BCIs with a variety of applications.